Timothy B. Dyk : the education of a federal judge - Dyk, Timothy B. (Anthem Press, an imprint of Wimbledon Publishing Company, 2022)
An account of what it was like to practice and adjudicate law in modern America, detailing shifts within the legal profession, both private and public, in the United States since the 1960s.